Vigna unguiculata: a productive option in the face of climate change? - Murga-Orrillo, Hipolito; Chuquimez Gonzales, Jhon K.; Pashanasi Amasifuén, Beto; Arévalo López, Luis A. (Frontiers in Agronomy, 2023)
Faced with the challenges of extreme climatic events and increasing food demand, cowpea farming offers a viable option for generating grains and foliage while aiding soil preservation. This research aimed to evaluate the impact of diverse organic fertilizers and plastic mulches on cowpea yields and soil macrofauna. A completely randomized block design was employed, with a factorial arrangement of 3x3+1, encompassing plastic mulch (3.5 mm) color (white, black, and blue), organic fertilizer (compost of chicken manure-agricultural soil-dolomite, island guano, and cattle manure compost), as well as a control (without synthetic mulch and organic fertilization). The study evaluated soil temperature, plant height, area biomass, foliar macronutrients, yield, and soil macrofauna. The findings demonstrate that soil temperature varies based on the color of the plastic mulch. It was observed that using organic fertilizers resulted in significantly taller plants than the control group, with fresh and dry biomass weight also being significantly greater (p<0.05) for cattle manure compost compared to the other treatments. Furthermore, the use of plastic mulches had an impact on soil macrofauna. Cowpea displayed resistance to low soil fertility and fluctuations in soil temperature ranging from <35°C to >40°C. However, high precipitation during the fruiting and harvesting seasons significantly impacted grain yields. Organic fertilizers produced noticeable variances (p<0.05) in the aerial biomass weight of cowpeas, particularly cattle manure compost. The data, indicates that soil macrofauna, like the earthworm Pontoscolex corethrurus, improved the availability of N, P, and K to the plant during the reproductive stage. Plastic mulches and organic fertilizers were linked to an increase in earthworm weights, specifically P. corethrurus. Additionally, plastic mulches served as a physical barrier against ants and bugs.